2015
DOI: 10.1093/europace/euv268
|View full text |Cite
|
Sign up to set email alerts
|

The risk of atrial fibrillation during right ventricular pacing

Abstract: HA pacing compared with RVA or RVS pacing seems to be associated with a lower risk of persistent/permanent AF occurrence. The risk of persistent/permanent AF was similar in the RVA vs. RVS groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 19 publications
1
75
0
4
Order By: Relevance
“…40 Of note, a retrospective study involving 477 consecutive patients who underwent PPM implantation for complete or advanced AVB demonstrated that RV pacing in the Hisian area compared with RV pacing in apical and septal positions was associated with lower risk of persistent / permanent AF after mean follow -up of nearly 5 years. 38 Importantly, the reported risk of chronic AF development was similar in both apical and septal RV pacing groups with the rate of progression at 25.7% and 28%, respectively. 38 In keeping with these findings, we found that the risk of permanent AF development was similar between patients with apical and nonapical RV lead position.…”
Section: Figure 3 Association Of Baseline Factors With Permanent Atrimentioning
confidence: 85%
See 3 more Smart Citations
“…40 Of note, a retrospective study involving 477 consecutive patients who underwent PPM implantation for complete or advanced AVB demonstrated that RV pacing in the Hisian area compared with RV pacing in apical and septal positions was associated with lower risk of persistent / permanent AF after mean follow -up of nearly 5 years. 38 Importantly, the reported risk of chronic AF development was similar in both apical and septal RV pacing groups with the rate of progression at 25.7% and 28%, respectively. 38 In keeping with these findings, we found that the risk of permanent AF development was similar between patients with apical and nonapical RV lead position.…”
Section: Figure 3 Association Of Baseline Factors With Permanent Atrimentioning
confidence: 85%
“…38 Importantly, the reported risk of chronic AF development was similar in both apical and septal RV pacing groups with the rate of progression at 25.7% and 28%, respectively. 38 In keeping with these findings, we found that the risk of permanent AF development was similar between patients with apical and nonapical RV lead position. Moreover, the analysis in patients who had a DDD PPM implanted during the last decade of the inclusion period showed similar results.…”
Section: Figure 3 Association Of Baseline Factors With Permanent Atrimentioning
confidence: 85%
See 2 more Smart Citations
“…A disadvantage of AV dyssynchrony encountered with this model-because of RV only pacing-is the potential for cardiac dysfunction and cardiomyopathy. There is a body of work that shows single chamber ventricular pacing and AVB can lead to increased risks of atrial fibrillation and decreased quality of life [17][18][19]. It is unknown what the longer-term effects of our model are and whether this could affect the outcomes of experiments assessed over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%